The role of the anterior nuclei of the thalamus in human memory processing. (July 2021) - Sweeney-Reed, Catherine M.; Buentjen, Lars; Voges, Jürgen; Schmitt, Friedhelm C.; Zaehle, Tino; Kam, Julia W.Y.; Kaufmann, Jörn; Heinze, Hans-Jochen; Hinrichs, Hermann; Knight, Robert T.; Rugg, Michael D.
Highlights: Neuroanatomical connectivity: anterior thalamic nuclei (ATN) in memory encoding. Lesion, animal, and neuroimaging studies support ATN involvement in memory. Human electrophysiology: active, selective role for ATN in memory formation. Frontal neocortex–ATN theta synchrony and theta–gamma coupling during encoding. Phase alignment to remembered stimuli suggests local ATN synaptic plasticity. Abstract: Extensive neuroanatomical connectivity between the anterior thalamic nuclei (ATN) and hippocampus and neocortex renders them well-placed for a role in memory processing, and animal, lesion, and neuroimaging studies support such a notion. The deep location and small size of the ATN have precluded their real-time electrophysiological investigation during human memory processing. However, ATN electrophysiological recordings from patients receiving electrodes implanted for deep brain stimulation for pharmacoresistant focal epilepsy have enabled high temporal resolution study of ATN activity. Theta frequency synchronization of ATN and neocortical oscillations during successful memory encoding, enhanced phase alignment, and coupling between ATN local gamma frequency activity and frontal neocortical and ATN theta oscillations provide evidence of an active role for the ATN in memory encoding, potentially integrating information from widespread neocortical sources. Greater coupling of a broader gamma frequency range with theta oscillations at rest than during memory encoding provides additional support for the hypothesis that the ATN play a role in selecting local, task-relevant high frequency activity associated with particular features of a memory trace.